Student Reflections on Learning in a Doctoral-Level Writing Course. - Anderson, Jessica; Berryman, Kristen; Dowd, Jessica; Kenny, Caitlin; Luib, Patrick; Nkrumah, Isaac; Reilly, Laura; Retano-Anderson, Angela; Ronquillo, Khristine; Wadhawan, Anju; Birnbaum, Shira (Nurse Educator)
Background: Programs to improve student writing have been deployed widely in nursing graduate education, but few operational indicators exist for measuring their value. Problem: The challenge of measuring outcomes reflects the complexity of what transpires when graduate students write. Better understanding is needed of what it means to students to "learn" from writing support. Approach: A full-semester writing course was implemented in a nursing science PhD program. In formative course assessment activities, students identified problems in early drafts of their work, which they subsequently learned to detect and resolve. In this article, students report what was learned. Conclusion: Writing skills, like clinical skills, are intertwined with intellectual maturation and sense of professional identity. Writing, like clinical learning, requires an investment of time and labor far beyond what is typical in didactic approaches to classroom-based graduate education. Our experience suggests a need to reconceptualize writing pedagogy in nursing.